2005
DOI: 10.1182/blood-2004-08-3198
|View full text |Cite
|
Sign up to set email alerts
|

B-cell recovery following rituximab-based therapy is associated with perturbations in stromal derived factor-1 and granulocyte homeostasis

Abstract: The occurrence of delayed neutropenia following rituximab is poorly defined and of unknown cause. We hypothesized it may be related to perturbations of stromal derived factor-1 (SDF-1) and granulocyte homeostasis. Late-onset neutropenia (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 32 publications
5
76
1
5
Order By: Relevance
“…They are also in agreement with sporadically published reports on BM biopsy findings in patients developing rituximab-associated LON. 4,6 Importantly, similar to our data, predominantly granulocytic hypoplasia with maturation arrest was a common finding in all studies. Therefore, clinicians should be aware of rituximab-induced LON and associated BM dysplasia to avoid a misdiagnosis of primary or secondary myelodysplastic syndrome (MDS).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…They are also in agreement with sporadically published reports on BM biopsy findings in patients developing rituximab-associated LON. 4,6 Importantly, similar to our data, predominantly granulocytic hypoplasia with maturation arrest was a common finding in all studies. Therefore, clinicians should be aware of rituximab-induced LON and associated BM dysplasia to avoid a misdiagnosis of primary or secondary myelodysplastic syndrome (MDS).…”
supporting
confidence: 91%
“…[1][2][3]6 However, published data are mainly based on small series and are often contradictory, perhaps due to the selective evaluation of isolated parameters. Our previous studies suggesting that LON in rituximab-treated lymphoma patients may be associated with T-cell large granular lymphocytic (T-LGL) proliferation [1][2] alluded to the possibility of altered T-cell responses associated with B-cell depletion induced by rituximab.…”
mentioning
confidence: 99%
“…14 Proteolytic enzymes such as neutrophil elastase, cathepsin G and matrix metalloproteinase-9 released from the activated neutrophils and monocytes can degrade and/or inactivate adhesion molecules such as VCAM-1/VLA-4, chemokines such as stromal-derived factor (SDF)-1/CXCR-4 and soluble Kit ligand, resulting in the disruption of contact between stem/progenitor cells and the bone marrow microenvironment, and then stem/progenitor cells would be released to migrate into peripheral blood. 14,15 However, recently late-onset neutropenia has been reported following rituximab-based chemotherapy, 22,23 and Dunleavy et al 24 have suggested that rituximab may induce perturbations of SDF-1/CXCR-4 interaction, which could retard the egress of neutrophils from bone marrow. Therefore, we investigated expression levels of adhesion molecules on PBSC in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although incubation of B cells with anti-CD20 antibody depletes normal circulating B cells and has variable effects on cell cycle progression and signaling, the detailed biologic functions of CD20 remain uncertain. 26 B-cell lymphopenia of approximately 6 months duration has been observed in 12/15 adult patients who received rituximab in preemptive indication, 8 and a few cases of prolonged hypogammaglobulinemia have been published, [27][28][29][30] of whom one provided laboratory evidence for similar mechanisms as described in the lymphoma setting. However, the situation may be more complex as additional factors may contribute following allogeneic HSCT, including engraftment, expansion and differentiation of lymphopoiesis, immunological processes between host and graft, the action of immunosuppressive agents and active EBV infection, which upon itself may be associated with immunodeficiency 31 and secondary graft failure as in two of the six patients described in this report.…”
Section: Discussionmentioning
confidence: 93%
“…), administered on days þ 1, þ 3, þ 6, þ 11. Primary engraftment was achieved in all patients and occurred after a median of 22.5 days (range, [16][17][18][19][20][21][22][23][24][25][26][27][28]; two patients had secondary graft failure at days 98 and 225 (patient nos. 2 and 4).…”
Section: Demographics and Transplant Characteristicsmentioning
confidence: 99%